PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ALAT-ALAT ISTRIK MEREK SCHNEIDER PADA PT. KAWI AGUNG KENCANA - Arwin Simon; Eva Elida Sembiring (Jurnal Akrab Juara, 2019)
Research takes object at PT. Kawi Agung Kencana by reason of the sale of PT. Kawi Agung Kencana is experiencing a decline in sales turnover, describing a low purchasing decision for PT. Kawi Agung Kencana due to product quality and prices that do not support. Researchers use marketing management theories, which relate to product quality, price and purchasing decisions. The method used in the study is a quantitative approach, this type of research is quantitative descriptive research and descriptive explanatory. The method of data collection is done by interview, questionnaire and documentation study. The purpose of this study was to examine and analyze the effect of product quality and price on the purchase decision of Schneider brand electrical equipment at PT. Kawi Agung Kencana. The analytical method used is multiple linear regression, simultaneous testing (F-test) and partially (T-test). The population used is the number of customers of 100 people, the number of samples used is 100 people. The sampling technique used is saturated sampling or census. The results showed that product quality partially had a significant positive effect on purchasing decisions while prices partially had no effect on purchasing decisions. Simultaneously shows the significant influence between product quality and price on purchasing decisions